الصورة الفنية في الرسائل الأندلسية في عهد الموحدين 541- 668ه : دراسة وصفية وتحليلية - أسعد، محمد جاسر جبالي (Kulliyyah Ma'arif al-Wahy wa-al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah, 2014)
This research aims at identifying the era of Almohad sovereignty, describing the situation in Andalusia in that era, exploring the different views on the artistic image, adopting a clear view to be a gateway into this study and presenting the stages of artistic image formation based on that particular view. This research aims also at introducing the authors of Andalusian essays in the era of Almohades, demonstrating the types of essays as well as their objectives and contents. The research then moves to studying the artistic images in these Andalusian essays, whereby it exposes the physical and cultural sources and the sensory patterns from which authors derived the artistic images that they used in their essays. The research also studies the forms related to the figures of speech and embellishments that are contained by the artistic images in Andalusian essays, with a demonstration of their types and effects on a particular artistic image and its meaning. The research also studies the most remarkable phenomena that appeared in the artistic image of the essays, as many phenomena related to the language of artistic images of the essays and their formation have emerged. The research is concluded by stating the most important findings and a set of recommendations, which may be useful for researchers who want to continue researching in the field of Maghrebian literature in general and prose in particular.